A Comparative Analysis of AutoCAD and NX Siemens Programs in Technical Drawing - Khasanov R.D (Zien Journals, 2023)
This scientific paper aims to analyze and compare the advantages of two prominent computeraided design (CAD) software programs, AutoCAD and NX Siemens, in the context of technical drawing. The paper explores the features, capabilities, and benefits offered by each software, highlighting their respective advantages in enhancing productivity, precision, and collaboration in the field of technical drawing. This analysis provides valuable insights for professionals, educators, and students in selecting the most suitable CAD software for their specific needs.
Keywords: AutoCAD; NX Siemens; technical drawing; computer-aided design